2017
DOI: 10.1002/jcu.22435
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left atrial function via two-dimensional speckle-tracking echocardiography in patients with coronary artery ectasia

Abstract: Our findings demonstrated that LA function may not be affected by CAE when assessed with 2DSTE. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 45:231-237, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…[ 26 ] In a recent study, Aghajani et al . [ 27 ] showed that the LA function as assessed by 2DSTE was not impaired compared with that in normal participants, which is concordant with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…[ 26 ] In a recent study, Aghajani et al . [ 27 ] showed that the LA function as assessed by 2DSTE was not impaired compared with that in normal participants, which is concordant with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Another study utilized 2D‐STE to assess the left atrium in patients with CAE compared with control subjects. The two groups did not differ regarding Sr, Scd, Sct, SRr, SRcd, and Sct 46 …”
Section: Resultsmentioning
confidence: 76%
“…The two groups did not differ regarding Sr, Scd, Sct, SRr, SRcd, and Sct. 46 3 Some issues should be considered in the interpretation of these findings.…”
Section: Caementioning
confidence: 99%